Petascale particle-in-cell simulations of kinetic effects in inertial fusion energy plasmas. (11th March 2019) - Wen, H; Tsung, F S; Mori, W B; Fonseca, R A; Silva, L O
Abstract: In this manuscript we describe new features in OSIRIS which allows us to simulate laser plasma interactions relevant to inertial fusion in 2D and quasi-3D. These features will allow for the simulation of laser plasma interactions with ever increasing realism and will finally allow for the quantitative comparison between large 2D/3D simulations and ongoing inertial fusion energy experiments with both kinetic electrons and ions in the near future.